Modeling of Tectonic-Thermal Evolution of Cretaceous Qingshankou Shale in the Changling Sag, Southern Songliao Basin, NE China - Liu, Yuchen; Liu, Bo; Cheng, LiJuan; Xing, Jilin; Tian, Shansi; Huang, Saipeng; Dong, Suying (Frontiers in Earth Science, 2021)
A series of significant shale oil discoveries have been made recently in the Upper Cretaceous Qingshankou Formation in the Songliao Basin, providing a new resource target for shale oil exploration in Northeast China. In this context, an understanding of the tectonic-thermal evolution and maturation history of the Qingshankou Formation is of great significance for shale oil exploration and evaluation. In this study, the thermal history of the Qingshankou Formation since the Late Cretaceous was reconstructed using the paleothermal indicator method. The results indicate that two stages of thermal evolution exist in the southern part of the Songliao Basin: 1) the gradual heating stage during the Late Cretaceous; the heat flow gradually increases during this period and reaches a maximum heat flow value at the end of the Cretaceous. 2) The decline stage since the Neogene; the tectonic activity is relatively stable and the geothermal heat flow is gradually reduced, and the present-day heat flow ranges from 60.1 to 100.7 mW/m2, with an average of 78.2 mW/m2. In addition, the maturity history of the organic-rich shale was reconstructed based on the new thermal history. The Cretaceous Qingshankou shales underwent deep burial thermal metamorphism at the end of the Cretaceous, whereas thermal has faded since the Neogene. The hydrocarbon generation and migration since the Late Cretaceous period of K2qn1 were modeled based on the maturity model. Two main cooling events took place in the late Nenjiang period and the late Mingshui period in the Changling sag. These two tectonic events controlled the structural style and the formation of shale oil reservoirs in the southern Songliao Basin.